Business Analysis of Dim Sum Fishery Products of the Poklahsar Kita Bisa Group in Ekor Lubuk Village, Padang Panjang District, Padang Panjang City, West Sumatra - Riani, Vovi; Darwis, Darwis; Zulkarnain, Zulkarnain (Faculty of Fisheries and Marine, Universitas Riau, 2025)
Fishery product processing is one of the agribusiness subsystems with excellent opportunities to increase fishery product yields. Poklahsar is a fishery product processing and marketing group. The products produced are barracuda/tete fish dim sum and shrimp dim sum. This research aims to analyze the amount of investment and profits in the fishery product processing business in Poklahsar Kita Bisa and the feasibility of the fishery product processing business in Poklahsar Kita Bisa. The method used is the case study method. The number of respondents used as the object of this research was 10 people, which was considered sufficient to obtain business analysis research data. The types of data collected include primary data and secondary data. This data was obtained from direct interviews using questionnaires and literature. The research results are as follows: 1) The total investment in the fishery product processing business was IDR 15,385,000, obtained from a fixed capital of IDR 12,737,000. Working capital IDR 2,648,000. 2) The total cost of the fishery product processing business is IDR 31.645.000, obtained from fixed costs of IDR 12.205.000 and variable costs of IDR 19.440.000. 3) Revenue from fishery product processing businesses amounting to IDR 52.800.000. 4) Revenue from the fishery product processing business is IDR 21.115.000. 5) Return Cost of Ratio (RCR) obtained a value of 1,66, Financial Rate of Return (FRR) of 137.24%, and the Payback Period of Capital (PPC) analysis obtained a result of 0.72, meaning it takes 7 months. So, based on the feasibility analysis, the fishery product dim sum business is based on existing provisions/criteria, and it can be concluded that this business is profitable and feasible to run